PENERAPAN PENDEKATAN KONTEKSTUAL DALAM PEMBELAJARAN KETERAMPILAN MENULIS PUISI SISWA KELAS V SDN 005 KOTO SENTAJO KECAMATAN SENTAJO RAYA - Ensiawati Ensiawati (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
Research problem is the low skill of writing poetry student in class V SDN 005 Koto Sentajo. The aim of thestudy is to improve poetry writing skills. The research method is classroom action research. The results of thefirst meeting data on the first cycle with a percentage of 39%, at the second meeting in cycle I percentage of61%, on the second cycle at the first meeting of 89% and increased to 93%, while the student activity on the firstcycle of the first meeting of 60% , increased to 71% at the second meeting. In cycle II, the first meeting of 89%increased to 92% student activity at the second meeting. Students complete in classical completeness of poetry inthe first daily re-completion reached 55% to 73% complete with classical thorough category. The conclusion ofthe research is that the application of contextual approach can improve poetry writing skills.